Fabricating Microsphere Lasers by Protein Dehydration: A Fast Fabrication Method and Excellent Lasing Properties - Toan, Nguyen Van; Nhat, Pham Van; Van Duong, Ta (VNU Journal of Science: Mathematics - Physics; Vol 37 No 4, 2021)
Microsphere biolasers have attracted a great deal of interest due to their potential in biosensing and cell-tracking. Various fabrication techniques have been explored for making microsphere biolasers, such as freeze-drying in a vacuum, standard oil in water dispersion procedure and protein dehydration in a solvent. The protein dehydration is highly interesting due to its simplicity and fast processing time. In this work, we demonstrate the fabrication of microsphere biolasers using protein dehydration in decanol and demonstrate that the fabrication process can speed up if the solvent is heated. When the solvent is heated to 60 °C, the fabrication time is reduced to half compared with the case when the sample is made at room temperature. Interestingly, while heating the solvent helps to decrease the fabrication time, it does not affect the lasing properties of the samples. The lasing thresholds of microsphere biolasers fabricated at 25 °C and 60 °C are similar. Furthermore, lasing operation under continuous pumping and lasing stability against storing time are also investigated. A typical 42 µm microsphere can still lase upon 2×10 4 excitation pulses. Lasers can work well after being stored for 12 weeks under ambient conditions.